HUBUNGAN DUKUNGAN KELUARGA DENGAN KUALITAS HIDUP PASIEN HIV/AIDS DI POLIKLINIK VCT RSUP SANGLAH DENPASAR - Antari, Kusuma (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
HIV/AIDS was an infectious disease with no cure. The disease also had a "window period" and the asymptomatic phase  (without symptoms) was  relatively  long in the disease process.  People  infected  with  HIV/AIDS  experienced  physical  problems,  psychological, increased dependency, social relationships, environment and spirituality.   The complexity of these  issues  resulted  in  a  decreased  quality  of  life  of  patients  wit h  HIV/AIDS.  This  study aimed to analyze the relationship between family support  and  quality of life of patients with HIV/AIDS in VCT Department of RSUP Sanglah Denpasar . This research was observational analysis  with  cross  sectional  approach  used  consecutive  sampling  technique,  and  sample obtained by  120  respondents.  This research was conducted on May 4 th –  June 4 th 2013. This research  used  guidance  of  Family  Support  and  WHOQOL-HIV  BREF  (World  Health Organization  Quality  of  Life-HIV  BREF)  questionnaires.  The  study  found  that  most respondents  (74,2%)  had  a  high   family  support  and  data  about  the  quality  of  life  for  the majority of respondents obtained results (70,8%) had a good quality of life.  Results of  ChiSquare statistical test at a significance level of ? = 0,05 obtained results p = 0, 000 (p < ?) and OR = 18,448,  means that there was  a relationship between family support  and  quality of life of  patients  with  HIV/AIDS  in  VCT  Department  of  RSUP  Sanglah  Denpasar .  Respondents who received family support 18 times higher chance to had a poor quality of life compared to respondents with high family support.
Keywords: Family Support, Quality of Life, Patients with HIV/AIDS